Prática de atividades físicas e custo do tratamento ambulatorial de diabéticos tipo 2 atendidos em unidade básica de saúde - Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2012)
Objectives: To observe differences in healthcare costs according to the level of physical activity in type 2 diabetes mellitus. Subjects and methods: A total of 121 type 2 diabetic patients were interviewed in two basic units of healthcare in Bauru, Brazil. Physical activity level was assessed by a questionnaire carried out during an interview. Costs of exams, medications and doctor and nurse visits were assessed for the previous year using invoices obtained from basic units of healthcare. Results: Sedentary type 2 diabetic patients presented higher costs for doctor visits (63%; p = 0.017) and medication to treat diseases other than diabetes (p = 0.001) than active patients. Conclusions: Sedentary type 2 diabetic patients presented higher healthcare costs related to doctor visits and medicine purchase.
Physical activity and healthcare cost of type 2 diabetic patients seen at basic units of healthcare
Keywords: Brazil; Costs analyzis; Motor activity; Type 2 diabetes mellitus